UTP Regulates the Cardioprotective Action of Transplanted Stem Cells Derived From Mouse Cardiac Adipose Tissue - Diaz Villamil, Esteban; De Roeck, Lucas; Vanorlé, Marion; Communi, Didier (Frontiers in Pharmacology, 2022)
Adipose tissue is a source of stem cells with a high potential of differentiation for cell-based regenerative therapies. We previously identified mouse P2Y2, an ATP and UTP nucleotide receptor, as a regulator of adipogenic and endothelial differentiation of cardiac adipose-derived stem cells (cADSC). We investigated here the potential involvement of P2Y2 receptor in the cardioprotective action of undifferentiated cADSC transplantation in mouse ischemic heart. Transplantation of cADSC was realized in the periphery of the infarcted zone of ischemic heart, 3 days after left anterior descending artery ligation. A strong reduction of collagen stained area was observed 14 days after cADSC injection, compared to PBS injection. Interestingly, loss of P2Y2 expression totally inhibits the ability of transplanted cADSC to reduce cardiac fibrosis. A detailed gene ontology enrichment analysis was realized by comparing RNA-sequencing data obtained for UTP-treated wild type cASDC and UTP-treated P2Y2-null cASDC. We identified UTP target genes linked to extracellular matrix organization such as matrix metalloproteinases and various collagen types, UTP target genes related to macrophage chemotaxis and differentiation into pro-fibrotic foam cells, and a significant number of UTP target genes linked to angiogenesis regulation. More particularly, we showed that UTP regulated the secretion of CCL5, CXCL5 and CCL12 chemokines and serum amyloid apolipoprotein 3, in the supernatants of UTP-treated cADSC. Interestingly, CCL5 is reported as a key factor in post-infarction heart failure and in the reparative and angiogenic action of transplanted ADSC on ischemic tissue. We investigated then if a UTP-pretreatment of cADSC amplifies their effect on cardiac revascularization in mouse ischemic heart. Transplantation of cADSC was able to increase peri-infarct capillary density, 14 days after their injection. This beneficial effect on cardiac revascularization was enhanced by a UTP-pretreatment of cADSC before their transplantation, and not observed using P2Y2-null cADSC. Our data support that the efficacy of transplanted cADSC can be regulated by the release of inflammatory mediators such as extracellular nucleotides in the ischemic site. The present study highlights the P2Y2 receptor as a regulator of cADSC cardioprotective action, and as a potential target for the therapeutic use of undifferentiated cADSC in post-ischemic cardiac ischemia.